2007
DOI: 10.1007/s11199-007-9280-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Aspects of Interpersonal Power and Relationship Functioning in Adolescent Romantic Couples

Abstract: This study used a multidimensional assessment of interpersonal power to examine associations between indices of relationship power and relationship functioning in 92 adolescent romantic couples recruited from rural communities in the Rocky Mountain region of the United States. Significant differences emerged between girlfriends and boyfriends in their reports of decision making authority, perceptions of humiliating behaviors by the partner, and ratings of themselves giving-in to their partners in a videotaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 61 publications
(66 reference statements)
5
68
0
5
Order By: Relevance
“…This is in line with findings reported by Galliher et al (1999) showing adolescent romantic relationships to be egalitarian when both partners contribute equal emotional resources and share power while interacting. However, in a recent study, adolescent girls were found to report lower levels of decision making authority, more perceptions of humiliating behavior by their partner, and described themselves as giving in to their partners (Bentley et al 2007). The sense of power adolescent girls experience and have in their romantic relationship needs to be further examined in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…This is in line with findings reported by Galliher et al (1999) showing adolescent romantic relationships to be egalitarian when both partners contribute equal emotional resources and share power while interacting. However, in a recent study, adolescent girls were found to report lower levels of decision making authority, more perceptions of humiliating behavior by their partner, and described themselves as giving in to their partners (Bentley et al 2007). The sense of power adolescent girls experience and have in their romantic relationship needs to be further examined in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…Men generally had more influence in sexual negotiations than women overall, but more traditional couples were less sexually self-disclosing, less communicative, and less effective at sexual negotiations than less traditional couples. Bentley et al (2007) also found that adolescent boys had more authority to make decisions than girls in their dating relationships and that those with more power were more sexually aggressive.…”
Section: Interpersonal Scriptsmentioning
confidence: 89%
“…Publications on heterosexual dating in Sex Roles over the last 10 years have included articles on dating behaviors, attitudes, and outcomes among and between particular social group members (e.g., Bentley et al 2007); dating scripts, including first-date scripts, rape scripts, and hookup scripts (e.g., Morr Serewicz and Gale 2008); media influences on dating (e.g., Zurbriggen and Morgan 2006), and dating violence and coercion (e.g., Maurer and Robinson 2008).…”
Section: Dating Research In Sex Roles From 2000 To 2010mentioning
confidence: 99%
“…The humiliating experience is one of being shamed, denigrated, or debased by another for reasons of the other's pleasure or desire to exert social power (Gilbert, 1998;Miller, 1996). In both the adolescent and adult literature, these relationship experiences have been linked to other negative outcomes, such as dating aggression and victimization (e.g., Bentley, Galliher, & Ferguson, 2007;Linder, Crick, & Collins, 2002).…”
Section: Global Self Reports Of Relationship Qualitymentioning
confidence: 99%